2000
DOI: 10.1007/s002340050892
|View full text |Cite
|
Sign up to set email alerts
|

MRA versus digital subtraction angiography in acute subarachnoid haemorrhage: a blinded multireader study of prospectively recruited patients

Abstract: We performed a blinded multireader study comparing MR angiography (MRA) with digital subtraction angiography (DSA) in 34 prospectively recruited patients who presented with acute subarachnoid haemorrhage (SAH). Two observers independently reviewed the MRA and DSA studies some months after clinical presentation. Presence of an aneurysm was rated on a 4-point confidence scale. Cases in which the initial interpretation of the observers varied were jointly reviewed to reach a consensus opinion. DSA was deliberatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Another small prospective study suggested that digital subtraction angiography and MRA were complementary. 110 However, in a review of the available literature, Wardlaw and White 111 concluded that "quality of data testing their [MRA and CTA] accuracy is limited." Thus, until better data become available, the appropriate technique for initial screening should be individualized; however, when it is clinically imperative to know if an aneurysm exists, catheter angiography remains the gold standard.…”
Section: Prevention Of Sahmentioning
confidence: 99%
“…Another small prospective study suggested that digital subtraction angiography and MRA were complementary. 110 However, in a review of the available literature, Wardlaw and White 111 concluded that "quality of data testing their [MRA and CTA] accuracy is limited." Thus, until better data become available, the appropriate technique for initial screening should be individualized; however, when it is clinically imperative to know if an aneurysm exists, catheter angiography remains the gold standard.…”
Section: Prevention Of Sahmentioning
confidence: 99%
“…The limitations of MRA compared with DSA include the limited spatial resolution and artifacts such as motion, susceptibility, and flow. 2 Nevertheless, an increasing number of recent studies suggest that DSA is no longer considered essential for establishing the diagnosis of cerebral aneurysms, 3,4 particularly when 3T MR imaging scanners are used. 2,5,6 Despite the continuing sophistication of the imaging technique, 1 important cause of the limited sensitivity of MRA is the detection failures of radiologists.…”
mentioning
confidence: 99%
“…32 This large heterogeneity in sensitivity and specificity estimates was also observed in this review, and subgroup analyses were performed in an attempt to identify potential sources of variation in study results. Three studies (Jäger et al, 17 Kouskouras et al, 18 and White et al 24 ) produced outliers in terms of sensitivity or specificity. Two of these used analog image evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these used analog image evaluation. 17,24 After excluding the studies by Jäger and White that evaluated images on hard copy films, diagnostic performance increased and heterogeneity decreased. Five of the 7 missed aneurysms >5 mm came from these 2 studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation